2018
DOI: 10.3390/ijerph16010088
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hospitalization Cost of Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Vietnam

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have been found to contribute, predominantly, to increasing costs of COPD—a major public health issue. This study aimed to fill the gap in literature concerning costs of AECOPD in Vietnam, by examining the direct cost of AECOPD hospitalization and determining potentially associated factors. A cross-sectional study was conducted at the Respiratory Center of Bach Mai Hospital, Hanoi. A total of 57 participants were selected. Information regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…The prevalence of diabetes in this study was underestimated due to the lack of screening programs for diabetes. Moreover, the prevalence of diabetes in this study is close to 12.3% reported by Ngo et al [ 24 ], lower than 25.3% reported by Terzano et al [ 25 ] and 26.3% reported by Perera et al [ 26 ]. Except for prevalence underestimation, comparing to the study of Terzano et al, this is probably due to younger age of participants in our study.…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of diabetes in this study was underestimated due to the lack of screening programs for diabetes. Moreover, the prevalence of diabetes in this study is close to 12.3% reported by Ngo et al [ 24 ], lower than 25.3% reported by Terzano et al [ 25 ] and 26.3% reported by Perera et al [ 26 ]. Except for prevalence underestimation, comparing to the study of Terzano et al, this is probably due to younger age of participants in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Another study conducted among patients hospitalized with acute coronary syndrome in eight Asian countries in 2013 found a mean length of stay of 10 days and per day cost in a critical unit that ranged from int $3210 in Singapore, int$ 284 in Thailand to int$ 98 in Vietnam [18]. For COPD patients, mean hospitalization costs were US$ 3,670 in China [16] and US$ 795 in Vietnam [17]. Our ndings are in the low range of these numbers with mean costs of INT $722 (sd=418), and cost per day below $100.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied factors that contribute to high inpatient costs in LMICs were age, gender, comorbidities, length of stay, and type of health care providers [15]. Disease-speci c factors that drive inpatient costs were type of stroke in China [16] and lung function for patients with COPD in Vietnam [17], both re ecting disease severity. Disease-speci c costing studies thus far were typically conducted in a single hospital and were limited by small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional Vietnamese study reported a statistically significant difference in mean total cost per hospitalization for an exacerbation of COPD between GOLD groups (6.4 million Vietnamese dong [VND] vs 14.1 million VND [p<0.05], for GOLD A and GOLD B, respectively). 59 A Danish registry study (2008–2017) reported total annual direct costs per patient to be higher in GOLD B versus GOLD A (€12,884 vs €8687, respectively) and lowest for GOLD A across all GOLD groups. 60 A Bulgarian study reporting indirect costs across GOLD A and B groups estimated that the total mean indirect costs per patient per year were higher for GOLD B versus GOLD A (€692.51 vs €575.11, respectively [p<0.001]).…”
Section: Resultsmentioning
confidence: 99%